Students' perceptions of fieldwork of local study ICSS in relation to vision 2020, Malaysia - Salleh, Mohamad Johdi; Abdul Rashid, Adnan; Mohamad, Baharom; Madin, Abu Bakar (2009)
Millions of Ringgit were allocated and spent by the government and the agencies to preserve and decorate the national heritage such as the museums, gallery, archives, sites, and other historicar-geographical remains. These were not wasteful when the record showed that local and international people were continuously visiting these sites located across the country. These are also became major tourist attraction which indirectly inculcated knowledge and enhanced appreciation upon the practices of multi-ethnic and multi-cultural Malaysian. Thus, this paper discusses a study on the students' perceptions of fieldwork approaches to Local Studies of the Integrated Curriculum for Secondary Schools (lCSS) Malaysia in. relation to the objectives of Vision 2020 and towards the development of first class human capital. The study was conducted in various types of schools in Perak and Terengganu which involved about eight hundred students. The instruments used were questionnaire and interview. The data was analysed by using SPSS and presented in percentage. The result of the study shows a high relation concerning the students' perceptions of fieldwork approaches and the objectives of Vision 2020, However, there were many wealmesses observed from the study and need effective solution as more students would benefit from the subject.